Serum toxicokinetics after intravenous and oral dosing of larkspur toxins in goats. (July 2017) - Welch, K.D.; Gardner, D.R.; Stonecipher, C.A.; Green, B.T.; Pfister, J.A.
Abstract: Poisoning of cattle by larkspur plants ( Delphinium spp.) is a concern for cattle ranchers in western North America. Previous research studies have evaluated the toxicokinetic profile of multiple larkspur toxins in several livestock species. However, those studies were all performed by orally dosing plant material. Consequently some toxicokinetic parameters could not be definitively determined. In this study, we compared the serum toxicokinetic profile of the larkspur alkaloids methyllycaconitine (MLA) and deltaline in goats dosed both IV and via oral gavage. The results from this study indicate that the toxic alkaloids in larkspurs undergo flip-flop kinetics, meaning the rate of absorption of the alkaloids is slower than the rate of elimination. The implications of flip-flop kinetics in treating animals poisoned by larkspur is discussed. Highlights: Larkspur alkaloids undergo flip-flop kinetics in orally dosed animals. There is no difference in the elimination and absorption rates of larkspur alkaloids when dosed as an extract or plant. The slow absorption rate of the larkspur alkaloids results in an extended mean residence time in animals (MRT). The extended mean residence time (MRT) impacts treatment of poisoned animals.